The Free and Combined Contents in Species of from Southeast Coast Amino Acid Caulerpa of India - Lewis, E J (Fishery Technology, 1965)
Caulerpa racemosa var. macrophysa, C. racemosa var cornyÂ· phora and C. scalpe/liformis are analysed by quantita.tive paper chromatographic technique for their amino acid contents in proteins, peptides and free state. It is found that no appreciable variation occurs in the quality of amino acid make up in these algae; but quantitative differences are apparent in them. Moreover, both qualitative and quantitative variations occur in the amino acid make up of the peptides, and in the free state. The results are compared with those of the other invesbigations.